Effect of Liquidity Management on Profitability of Commercial Banks in Nigeria (2021)
Commercial banks in Nigeria are more engrossed with profit maximization and as such they tend to neglect the importance of liquidity management. This eventually leads to financial indebtedness and consequently low patronage and deposit flight. This study examined the effect of liquidity management on profitability of commercial banks in Nigeria using data obtained from the financial statements of tier 1 banks over the period 1998 to 2018. The study employed the correlational research design and engaged the Johansen test with the vector error correction model to access the long run and short run relationship among the variables. The results of the Johansen test revealed at most two cointegrating equations among the variables, while result of vector error correction revealed a positive effect of liquidity on return on asset and return on equity but a negative effect on net profit margin. Results revealed a fairly stable trend in the liquidity and profitability indicators from 1998-2018 and concluded that banks controlled enough liquidity to serve their obligations. The study recommends that the central bank of Nigeria should maintain the regulation over the minimum liquidity of commercial banks as this affects their profitability